2023
DOI: 10.3389/fimmu.2023.1127349
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial infusion chemotherapy combined with anti-PD-1/PD-L1 immunotherapy and molecularly targeted agents for advanced hepatocellular carcinoma: a real world study

Abstract: BackgroundMolecular targeted therapy combined with immunotherapy significantly improves the prognosis of patients with advanced liver cancer. Additionally, hepatic arterial infusion chemotherapy (HAIC) can improve the prognosis of patients with advanced liver cancer. This real-world study aimed to evaluate the clinical efficacy and safety of HAIC combined with molecular targeted therapy and immunotherapy in the treatment of primary unresectable hepatocellular carcinoma (uHCC).MethodsA total of 135 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
8
1
Order By: Relevance
“…In multivariate analysis, extrahepatic metastasis and Child-Pugh classification were independent prognostic factors for PFS. The results were worse than in previous studies [ 24 , 25 ]. The main reasons for the difference may be the following: the current study not only included HCC with PVTT, but also patients with hepatic vein and vena cava tumor thrombus, which accounted for 25%, and the average HAIC cycles received in this study was less than that of the studies before.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In multivariate analysis, extrahepatic metastasis and Child-Pugh classification were independent prognostic factors for PFS. The results were worse than in previous studies [ 24 , 25 ]. The main reasons for the difference may be the following: the current study not only included HCC with PVTT, but also patients with hepatic vein and vena cava tumor thrombus, which accounted for 25%, and the average HAIC cycles received in this study was less than that of the studies before.…”
Section: Discussioncontrasting
confidence: 96%
“…Another clinical trial that enrolled 247 HCC patients with portal vein invasion indicated that sorafenib plus HAIC has significantly longer OS when compared with sorafenib monotherapy (13.37 months vs. 7.13 months) [ 24 ]. More and more studies are trying to explore the safety and efficacy of the combination of HAIC, anti-PD-1/PD-L1 immunotherapy, and molecularly targeted agents and find the promising benefits of these combinations [ 25 , 26 ]. However, no study focuses on HCC patients with macrovascular invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to upfront surgery, patients receiving neoadjuvant targeted immunotherapy have a statistically significant increase in postoperative nononcologic mortality, but the difference is relatively small and may decrease with an increase in sample size. Numerous studies have shown that targeted immunotherapy is safe and well-tolerated 41 , 42 , and our two study groups did not have a significant difference in the occurrence of other major postoperative complications, indicating the safety of neoadjuvant targeted immunotherapy. Additionally, even though there is a slight increase in the risk of postoperative nononcologic mortality with neoadjuvant targeted immunotherapy, this risk is accidental and can be improved.…”
Section: Discussionsupporting
confidence: 55%
“…For antiangiogenic therapy, the patients were administered 8 mg of lenvatinib orally once daily, sorafenib 200 mg twice daily, and apatinib 250 mg once daily. Please refer to our previously published 001 Research for detailed treatment of patients ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that for primary unresectable HCC, HAIC treatment combined with targeted therapy and immunotherapy can achieve a significant surgical conversion rate ( 14 , 15 ). Although these findings are optimistic for individuals with unresectable HCC, it is important to note that not all patients may benefit from this combination therapy.…”
Section: Introductionmentioning
confidence: 99%